A review: the role of remote sensing in precision agriculture - Liaghat, Shohreh; Balasundram, Siva Kumar (Science Publications, 2010)
Precision agriculture is an emerging farm management strategy that is changing the way people farm. At present, there is an increasing commitment to reduce reliance on excessive chemical inputs in agriculture. Numerous technologies have been applied to make agricultural products safer and to lower their adverse impacts on the environment, a goal that is consistent with sustainable agriculture. Precision agriculture has emerged as a valuable component of the framework to achieve this goal. This review highlighted on remote sensing technology and describes how it can be used as an effective tool in precision agriculture.